Estudo teórico e experimental da secagem de louças sanitárias em baixas temperaturas - Gomez, Ricardo Soares (2023)
Drying is a heat and mass transfer operation involving the removal of moisture, being an important and expensive task in the manufacturing process of several products. For ceramic materials, the drying process is necessary to remove the water that is added to the clay in the molding stage and to provide the necessary strength to reduce the chances of failure during the product firing stage. For sanitary ware, it is necessary to carry out a pre-drying stage immediately after removing the part from the mold, in an environment with a temperature between 30 and 40ºC, resulting in an additional energy cost. This thesis aims to study, both theoretically and experimentally, the low-temperature drying process of sanitary wares, especially sanitary toilets. Seven drying experiments were carried out in an oven under different operating conditions (temperature, relative humidity; natural and forced convection). Subsequently, an empirical mathematical modeling and calculations were performed to evaluate the drying performance. The experimental results indicate that increasing the temperature and reducing the relative humidity of the air lead to faster drying. It was found that for certain physical situations, it is more advantageous to focus on reducing the relative humidity of the drying air rather than seeking solutions to increase its temperature. Furthermore, no cracks or fissures were observed during the experiments, and an inverse linear correlation was found between linear retraction and moisture content, whereby moisture loss is accompanied by sample shrinkage. Finally, the results of the average specific energy consumption (ASEC) indicate that the lower the drying air temperature, the more efficient the process. However, within the temperature range studied, the maximum relative difference in ASEC between experiments was less than 3%, indicating that other factors should be considered in defining the operational conditions of the air in the pre-drying sector of sanitary ware, such as processing time, weather conditions, and market demand for the product.